Comparison of complication and success rates of perclose proglide device with surgical cut down in patients undergoing TAVI and TEVAR/EVAR Procedures - Jamal Moosavi; Somaye Ahmadi; Parham Sadeghipour; Ata Firoozi; Bahram Mohebbi; Omid Shafe; Hooman Bakhshandeh Abkenar; Ahoura Salehi Nobandegani (Annals of Circulation - Peertechz Publications, 2022)
Background: The Common Femoral Artery (CFA) is the most frequently used peripheral artery for Trans-catheter aortic valve implantation (TAVI) and Endovascular Aortic Repair (EVAR)/ Thoracic Endovascular Aortic Repair (TEVAR) procedures. CFA access hemostasis could be obtained by manual compression, surgical cut-down, or using arteriotomy closure devices, including ProGlide. Method: During a retrospective cohort study we compared ProGlide with surgical cut-down hemostasis in 225 patients who underwent TAVI or EVAR/TEVAR, including 290 access sites, during a 10 years period in terms of access site complications, procedure length and post-procedural hospitalization duration. Results: The success rate of hemostasis was 100% in the PP device group and 98.3% in the SCD group. The mean Procedure length was significantly shorter in ProGlide device hemostasis and the mean post-procedural hospitalization length had a non-significant difference between the two groups. Access site complications occurred in 21.1% of the ProGlide group and 26% of the SCD group.  Conclusion: Perclose ProGlide device is safe and effective for access site closure in procedures that need large sheaths and it is non-inferior to standard surgical cut-down. Training, experience and careful application of the device have significant importance in ensuring successful hemostasis.